Is it given over importance to serum zinc level in patients with sepsis? Zinc and sepsis - Yildiz, Hamit (Progress in Nutrition, 2019)
Background: Sepsis is a systemic inflammatory response to infection, life-threating and one of leading causes of death in intensive care units. The aim of this study is to determine relation between mortality and daily required doses of zinc replacement in adult patients with sepsis. Subjects and Methods: This retrospective study was carried out in internal medicine intensive care unit (ICU) of Gaziantep University Hospital. A total of 264 patients patients with sepsis in ICU, who are with low serum zinc level at admission (n=132) and not (n=132) included in the study. Results: 28 and 90-day mortality have been found higher in patients with normal serum zinc level at admisson to ICU than other group as 53.8% and 91.8%, respectively (p